2004
DOI: 10.1097/01.pcc.0000137987.74235.5e
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis Predictors of outcome in a pediatric intensive care unit of a developing country*

Abstract: Two thirds of children with diabetic ketoacidosis in our series had new-onset diabetes, and 13.2% died. Serum osmolality at admission was the most important predictor of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
4
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 30 publications
3
67
4
2
Order By: Relevance
“…[7] Most common presenting complaints was fever followed by vomiting and rapid breathing, in contrast to impaired level of consciousness as reported by jayshree etal. [10] History of symptoms of polyuria and polydipsia were given in only 5 (16.6%) cases as opposed to other studies [3,7] which reported it to be 25% and 85% respectively. Most of our patients had new onset type 1DM.…”
Section: Resultsmentioning
confidence: 60%
“…[7] Most common presenting complaints was fever followed by vomiting and rapid breathing, in contrast to impaired level of consciousness as reported by jayshree etal. [10] History of symptoms of polyuria and polydipsia were given in only 5 (16.6%) cases as opposed to other studies [3,7] which reported it to be 25% and 85% respectively. Most of our patients had new onset type 1DM.…”
Section: Resultsmentioning
confidence: 60%
“…The mortality rate in DKA is between 0.15% and 0.35% in the developed countries, such as the United States of America, Canada and the UK (6)(7). This rate is between 3.4% and 13.4% in the countries such as India, Pakistan and Bangladesh (8)(9)(10)(11). These differences may be due to the differences in the duration of feeling bad before referring to a hospital, the improper treatments, and the differences in the medical care received by patients with DKA.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] In this study group the mortality rate was 12.8%. The socio demographic factors like age group, sex, geographical area, consanguinity of parents was not significantly associated with mortality in this study.…”
Section: Discussionmentioning
confidence: 99%